Balanced Nutrition Behavior Relationship With Hypertension Incidence In Sugiharjo Village Batang Kuis District - Ginting, Wira Maria; Silaban , Sidi Mastiur (Sean Institute, 2022)
Nutritional problems that are not optimal are related to poor health. Poor nutrition is a risk factor such as cardiovascular disease (heart and blood vessel disease, hypertension and stroke), and eating behavior in food selection will affect a person's nutritional state. This study is a quantitative study that aims to determine the behavior of balanced nutrition with the incidence of hypertension in Sugiharjo Village, to determine the relationship between balanced nutrition behavior and the incidence of hypertension in Sugiharjo Village. The inclusion criteria of Sugiharjo Village residents were 35 people. This study shows that there are 22 (62.9%) female respondents compared to 13 male respondents (37.1%). The number of samples was determined using the Lameshow formula, namely 35 people. The data was taken using a questionnaire including food recall with direct interviews. Data analysis used univariate analysis and bivariate analysis which was processed using the SPSS program and presented in tabular form. The results of the study using the chi-square test showed that there was a relationship between balanced nutrition behavior and the incidence of hypertension in Sugiharjo village, Batang Kuis district. The p-value is 0.048, which means it is smaller than 0.05. Thus, it can be concluded that there is a relationship between balanced nutrition behavior and the incidence of hypertension in Sugiharjo Village.